Rekonstruksi Kepemimpinan Bangsa: Strategi Integrasi Teknologi Digital dan Kearifan Lokal di Sekolah Dasar - Aba, Akbar; Muhammad Yusuf; Fajrul Khaer; Ilmiawan; Saqjuddin; Ilham Samudra Sanur (Education Management: Jurnal Manajemen Pendidikan Islam, 2025)
This research aims to explore the strategic role of educational leadership in maintaining national identity through the integration of technology and local wisdom in Indonesian primary schools. The study also highlights the gap in technology access between urban and rural areas and the challenges in curriculum development that can harmonize local cultural values with digital advancements. Using the literature review method, this study analyzes various literatures to understand the contribution of educational leadership to integrative policies that favor the preservation of national identity in the digital era. The findings show that educational leadership plays a central role in designing policies that not only encourage the use of technology, but also instill noble values of national culture. However, there are still significant barriers such as limited digital infrastructure, lack of locality-based teacher training, and lack of community involvement in curriculum formulation. Therefore, this study recommends strengthening inclusive policies, equitable technology investment, contextual teacher training and close collaboration with local communities to realize basic education that is firmly rooted in the nation's culture while being adaptive to the times.